Implementation of Full Systematic Land Registration Policy : Study in Bunut District, Pelalawan Regency - Priyo Budi Maryoso (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Implementation of Complete Systematic Land Registration (PTSL) in Bunut District is one of the biggest PTSL activity targets at the Pelalawan Regency Land Office for the 2021 fiscal year, namely 7,964 Land Rights Certificates (SHAT), however the realization achieved was only 3,728 Certificates (K1). Because of this, the research is intended to examine how Complete Systematic Land Registration (PTSL) activities are implemented in Bunut District and what factors hinder the Implementation of Complete Systematic Land Registration (PTSL) activities in Bunut District. The theoretical concept used is the Policy Implementation Theory according to the Theory of George C. Edward III. This research uses a qualitative method with descriptive data analysis. Data collection techniques are carried out using interviews, observation and documentation. Data analysis techniques with stages of data collection, data reduction, data display and confirmation of conclusions. The research results show that the implementation of Complete Systematic Land Registration (PTSL) activities in Bunut District is in accordance with Standard Operating Procedures (SOP) based on Minister of ATR/Head of BPN Regulation No. 6 of 2018 concerning PTSL and there are several obstacles in its implementation including: Lack of human resources at the Pelalawan Regency Land Office, lack of enthusiasm regarding the imposition of BPHTB, the existence of plots of land that enter or intersect with PIPPIB areas and forest areas, the imposition of PTSL preparation costs, land owners who are not available or cannot be contacted.